Answer:
v =√[2g*L (1-cosθ)]
Step-by-step explanation:
To solve this question, we would be using the law of energy conservation equation. The law of energy conservation is mathematically written as
Ek1 + Ep1 = Ek2 + Ep2, where
Ek1 is the kinetic energy, which is also Zero
Ep1 is the potential energy which is represented by the formula, m*g*L*cosθ
Ek2 is also the kinetic energy, given as ½m*v^²
Ep2 is the potential energy with the formula, m*g*L
If we substitute the defined equations into the primary equation, we have
0 - m*g*L*cosθ = ½m*v^² - m*g*L
½mv² = m*g*L - m*g*L*cosθ
½mv² = m*g*L (1-cosθ)
v² = 2g*L (1-cosθ)
v =√[2g*L (1-cosθ)]